2021
DOI: 10.1063/5.0056449
|View full text |Cite
|
Sign up to set email alerts
|

Probing dynamics of nanoparticle chains formation during magnetic hyperthermia using time-dependent high-frequency hysteresis loops

Abstract: The heating power of magnetic nanoparticles (MNPs) submitted to high-frequency magnetic fields is generally probed using calorimetric methods, which suppose that the heating power does not evolve with time. Among the several parameters governing MNP heating properties, their organization into chains under the influence of the applied magnetic field is of key importance, though the dynamic of this phenomenon has been rarely studied experimentally. In the present article, time-resolved high-frequency hysteresis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…The authors attribute this behaviour to the formation of chains that are observed by TEM. 28 More recently, Mille et al 29 reported chain formation during magnetic hyperthermia using time-dependent high-frequency hysteresis loops in 17 nm FeNi 3 nanoparticles and observed that the chains are formed on a timescale ranging from several tens of seconds to less than 100 ms. This chain formation strongly depends on the magnetic field amplitude but does not depend on the frequency in the studied range (from 9 to 78 kHz).…”
Section: Introductionmentioning
confidence: 99%
“…The authors attribute this behaviour to the formation of chains that are observed by TEM. 28 More recently, Mille et al 29 reported chain formation during magnetic hyperthermia using time-dependent high-frequency hysteresis loops in 17 nm FeNi 3 nanoparticles and observed that the chains are formed on a timescale ranging from several tens of seconds to less than 100 ms. This chain formation strongly depends on the magnetic field amplitude but does not depend on the frequency in the studied range (from 9 to 78 kHz).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, abnormal phenomena appeared at magnetic field strengths below 1.5 mT, where NP showed unexpected ∆T results. This might be due to the chains' formation effect discussed in Mille et al [21]. This should be investigated further to determine if the cause is the exposure time, B, to what extent the MNPs' concentration has an effect on the formation of the chains, and if the waveform shape has any impact on it.…”
Section: Discussionmentioning
confidence: 95%
“…The iron oxide superparamagnetic nanoparticles (SPIONs) showed a high specific absorption rate (SAR), a 72% loading efficiency and a slow and sustained release in a pH-dependent manner over a period of time, making them suitable for MHT and controlled drug delivery. In Mille et al [21], the NP chain formation during MHT through the calorimetric method was studied using time-resolved high-frequency hysterisis loops. The study proved that the formation of the chains is dependent on time and magnetic field amplitude, whereas it is not dependent on the frequency in the range they experimented (between 9 and 78 kHz).…”
Section: Introductionmentioning
confidence: 99%
“…MNPs have been shown to be extremely valuable tools, with a wide variety of uses in engineering 16 , 34 , 35 and medicine. 1 , 36–38 They have been utilized as reusable catalysts, 39 , 40 in situ diagnostic agents, 41 contrast agents for magnetic resonance imaging, 42 and for therapeutic hyperthermia 14 , 16 , 21 , 43 , 44 – to name but a few noteworthy examples. In response to the application of a magnetic field, MNPs form chains then clusters which move at varying speeds depending on the magnetic properties of the particles, internal particle–particle interactions, particle–surface interactions, and magnetic field conditions.…”
Section: Discussionmentioning
confidence: 99%